Volcanic dust veils from sixth century tree-ring isotopes linked to reduced irradiance, primary production and human health - Samuli Helama; Laura Arppe; Joonas Uusitalo; Jari Holopainen; Hanna M. Mäkelä; Harri Mäkinen; Kari Mielikäinen; Pekka Nöjd; Raimo Sutinen; Jussi-Pekka Taavitsainen; Mauri Timonen; Markku Oinonen (NATURE PUBLISHING GROUP, 2022)
The large volcanic eruptions of AD 536 and 540 led to climate cooling and contributed to hardships of Late Antiquity societies throughout Eurasia, and triggered a major environmental event in the historical Roman Empire. Our set of stable carbon isotope records from subfossil tree rings demonstrates a strong negative excursion in AD 536 and 541-544. Modern data from these sites show that carbon isotope variations are driven by solar radiation. A model based on sixth century isotopes reconstruct an irradiance anomaly for AD 536 and 541-544 of nearly three standard deviations below the mean value based on modern data. This anomaly can be explained by a volcanic dust veil reducing solar radiation and thus primary production threatening food security over a multitude of years. We offer a hypothesis that persistently low irradiance contributed to remarkably simultaneous outbreaks of famine and Justinianic plague in the eastern Roman Empire with adverse effects on crop production and photosynthesis of the vitamin D in human skin and thus, collectively, human health. Our results provide a hitherto unstudied proxy for exploring the mechanisms of 'volcanic summers' to demonstrate the post-eruption deficiencies in sunlight and to explain the human consequences during such calamity years.